Contribution to the anthropological, ethnographic and linguistic study of the Kashuiéna Indians, as well as acculturation phenomena - Polykrates, Gottfried (Revista do Museu de Arqueologia e Etnologia, 2021)
Text based on visits realized by Polykrates, in the years 1957 and 1958-59 at to the so-called Kashuiéna Indians (Katxuyana), residents of the Cachorro river. Initially, this author addresses anthropological aspects, more precisely related to physical anthropology, in which he highlights aspects of the morphology of people's feet, as well as the morphology of the body in general and the physical appearance of the residents of the villages visited. It also features a quick characterization of your way of life and a list of words in the local language. Finally, it describes some situations that, according to the author, reveal a rapid process of acculturation reaching the visited group.